Long-term survival of an advanced gastric cancer patient with multiple liver metastases following maintenance therapy with envafolimab and oral chemotherapy: a case report - Wang, Sen; Zong, Heng; Wu, Linlin; Wei, Yuandong; Wang, Heng (Frontiers in Oncology, 2025)
The survival of advanced gastric cancer with liver metastases has a grim outlook, especially in tumors which are immune cold like with HER2 negativity, PD-L1 CPS less than 1, microsatellite stable, and low tumor mutational burden. A 65-year-old patient with poorly differentiated gastric adenocarcinoma having several hepatic metastases and stage IV which stopped the first-line FOLFOX because of grade III gastrointestinal toxicity and myelosuppression is reported in this case. Molecular profiling affirmed an immune cold phenotype, and individualization of the maintenance regimen to weekly subcutaneous envafolimab and oral S-1 was induced. This was treated well and the laboratory parameters were stable thus there were no serious adverse event related to immune reactions. Serial imaging showed sustained regression and stabilization of hepatic metastases, total regression of primary lesion of the gastric lesion, and nonexistent disease. The patient had 46 months of overall survival time with a good performance status. This case recommends that maintenance therapy comprising of both PD-L1 blockage and oral fluoropyrimidine can serve as long-duration disease control and significant long-term advantage to a subset of the patients with metastatic immune-cold gastric cancer.